Medical Record Service Management: Interface Design Integrated Application and Registration System Research Unit: Manajemen Pelayanan Rekam Medis : Interface Design Sistem Permohonan Dan Registrasi Terintegrasi Unit Penelitian - Rohman, Hendra; Nurrochman, Alwhan (Procedia of Engineering and Life Science, 2025)
Applications for scheduling research in the Diklit section are still manual, resulting in the process of arranging researchers having to go back and forth between officers which takes a long time. When the payment process has been carried out, the researcher returns to the Medical Records Installation and meets the research officer for registration and determining the date the research will be carried out. Researchers still have to come back to the research section of the Medical Records Installation one day before the research is carried out to write down the data on borrowing medical record files by filling in the tracers manually one by one so that the officers can prepare them on the day the research is carried out by the researchers. The aim is to create an interface design for an integrated application and registration system for research units. The result is an interface design for the research scheduling application process by researchers who can anticipate queues (online registration). Interface design for the application validation process by officers. The interface design of the researcher’s email confirmation of the application is validated. The interface design of the registration process by researchers after validation shows that the research records include medical records that will be used by researchers whether using eMR, BRM or both. When using BRM, the researcher writes down the number of BRM and then a tracer template will appear according to the amount that must be filled in and later printed by the officer for taking the BRM from the storage shelf. The interface design of the researcher’s email confirmation of successful registration contains the day, date and time the research can be carried out to make it easier for the researcher to come at the available time. The interface design for registration data sent to officers displays data on the number of applications, validated applications, number of daily visitors, and print reports. Conclusion: the interface design that has been designed can be taken into consideration in developing an information system in the research field involving the medical records work unit